Agriculture marketing trends in India: challenges and prospects (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Market signals drove market players to alter their marketing methods in order to offset the negative externalities that damage ecological sustainability, both inside and outside the system. With the advent of environmentalism, marketing has become more complicated, and marketers must now deal with the problems and possibilities that come with changing customer needs. This research is both explanatory and descriptive. It adheres to the theoretical aspects' descriptive model. It includes significant current literature to improve the results of literature evaluations. Comprehensive Literature Review The review of the relevant literature illuminates and brings our study issue into closer focus. Our strategy has been enhanced, and our knowledge base has grown as a consequence. The findings indicated that there are several challenges to overcome when seeking to join the rural market. The primary purposes are as follows: first, to transport goods to faraway locations; second, to meet the needs of destitute areas; and third, to provide storage facilities for the items.